2004
DOI: 10.1074/jbc.m404169200
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Resonance Energy Transfer Analysis of Subunit Stoichiometry of the Epithelial Na+ Channel

Abstract: Activity of the epithelial Na ؉ channel (ENaC) is ratelimiting for Na ؉ (re)absorption across electrically tight epithelia. ENaC is a heteromeric channel comprised of three subunits, ␣, ␤, and ␥, with each subunit contributing to the functional channel pore. The subunit stoichiometry of ENaC remains uncertain with electrophysiology and biochemical experiments supporting both a tetramer with a 2␣:1␤:1␥ stoichiometry and a higher ordered channel with a 3␣:3␤:3␥ stoichiometry. Here we used an independent biophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 31 publications
3
49
0
Order By: Relevance
“…In agreement, several studies reported that the related epithelial Na + channel (ENaC) is composed of four (18)(19)(20)(21) or nine subunits (22)(23)(24). In strong contrast, however, the crystal structure of chicken ASIC1 revealed a number of three subunits (12,25), suggesting that all ASICs and their relatives like ENaC are trimers.…”
mentioning
confidence: 69%
“…In agreement, several studies reported that the related epithelial Na + channel (ENaC) is composed of four (18)(19)(20)(21) or nine subunits (22)(23)(24). In strong contrast, however, the crystal structure of chicken ASIC1 revealed a number of three subunits (12,25), suggesting that all ASICs and their relatives like ENaC are trimers.…”
mentioning
confidence: 69%
“…Another involved analysis of the sizes of intramembranous particles visualized by freeze fracture followed by electron microscopy (11). Notably, a trimer-of-trimers structure would also explain coimmunoprecipitation and FRET data, showing that ENaC contains at least two copies of each subunit (31). Evidence for the functional relevance of a 'triple-barrel' organization of ENaC has also been presented, indicating that the trimer-of-trimers structure reported here might be physiologically relevant (32).…”
Section: Discussionmentioning
confidence: 95%
“…Our experimental design and rationale for determining subunit stoichiometry closely followed that of Zheng and colleagues [16,17], Staruschenko and colleagues [13], and Kerschensteiner and colleagues [19]. Zheng et al (2002) and Kerschensteiner et al (2005) successfully used a FRET method in the determination of a fixed stoichiometry of 3:1 for the rod cyclic-nucleotide gated channels and heteromeric Kv2.1/Kv9.3 channels, respectively.…”
Section: Stoichiometry Of Asic Channelmentioning
confidence: 99%
“…The efficiency of energy transfer falls off with the sixth power of the distance between the donor and acceptor molecules [14]. FRET has been successfully employed as a molecular ruler in investigations of the stoichiometry, assembly, and conformational arrangement of many types of receptors and channels [13,[15][16][17][18][19]. Another advantage of FRET over biochemistry approaches such as co-IP is that FRET measurement is non-invasive, allowing determination of subunit stoichiometry from intact channels in the cell membrane.…”
mentioning
confidence: 99%
See 1 more Smart Citation